Response of carbon fluxes to water relations in a savanna ecosystem in South Africa - (:unkn) unknown (My University, 2008)
The principal mechanisms that connect carbon fluxes with water relations in savanna ecosystems were studied by using eddy covariance in a savanna ecosystem at Kruger National Park, South Africa. Since the annual drought and rewetting cycle is a major factor influencing the function of savanna ecosystems, this work focused on the close inter-connection between water relations and carbon fluxes. Data from a nine-month measuring campaign lasting from the early wet season to the late dry season were used. Total ecosystem respiration showed highest values at the onset of the growing season, a slightly lower plateau during the main part of the growing season and a continuous decrease during the transition towards the dry season. The regulation of canopy conductance was changed in two ways: changes due to phenology during the course of the growing season and short-term acclimation to soil water conditions. The most constant parameter was water use efficiency that was influenced by VPD during the day but the VPD response curve of water usage did change only slightly during the course of the growing season and decreased by about 30% during the transition from wet to dry season. The regulation of canopy conductance and photosynthetic capacity were closely related. This observation meets recent leaf-level findings that stomatal closure triggers down-regulation of Rubisco during drought. Our results may show the effects of these processes on the ecosystem scale.
Keywords: African Research